Research progress on the role of extracellular vesicles in the pathogenesis of diabetic kidney disease - Jiangyuan Jin; Mianzhi Zhang (Renal Failure)
Diabetic kidney disease (DKD) is a serious complication of diabetes mellitus (DM) and has become the main cause of end-stage renal disease worldwide. In recent years, with the increasing incidence of DM, the pathogenesis of DKD has received increasing attention. The pathogenesis of DKD is diverse and complex. Extracellular vesicles (EVs) contain cell-derived membrane proteins, nucleic acids (such as DNA and RNA) and other important cellular components and are involved in intercellular information and substance transmission. In recent years, an increasing number of studies have confirmed that EVs play an important role in the development of DKD. The purpose of this paper is to explain the potential diagnostic value of EVs in DKD, analyze the mechanism by which EVs participate in intercellular communication, and explore whether EVs may become drug carriers for targeted therapy to provide a reference for promoting the implementation and application of exosome therapy strategies in clinical practice.